PENGARUH RASIO KEUANGAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP DEVIDEN PAYOUT RATIO PERUSAHAAN OUTOMOTIVE - Harianto, Budi (Universitas muhammadiyah palembang, 2012)
This study aims to determine the effect of financial ratios Debt Equity Ratio (DER), Current Ratio (CR), Return On Equity (ROE), and the Firm's Growth Dividend Payout Ratio outomotive companies in Indonesia Stock Exchange. There are two problems in this research that the first is there a significant effect of Debt Equity Ratio (DER), Current Ratio (CR), Return On Equity (ROE), and the Growth Company jointly against the Dividend Payout Ratio, and the second is there any influence significant Debt Equity Ratio (DER), Current Ratio (CR), Return On Equity (ROE), and partially on Company Growth Dividend Payout Ratio. The data used in this study is the Company's financial statements for the year 2005-2009 for the 12 companies in the stock outomotive Securities Indonesia, using multiple regression analysis, the normality test, and testing the assumptions of classical test of autocorrelation, multikolenieritas, heteroskedastisitas, who assisted analysis tool SPSS for Windows ver. 17 with signifikan5% level. Based on research results and the classical assumption of normality of data, obtained results that the data used normal and free from multikolenieritas, heteroskedastisitas, and autocorrelation, then to answer the problem in this study tested the hypothesis and the first results obtained jointly financial ratios Debt Equity Ratio (DER), Current Ratio (CR), Return On Equity (ROE), and growth significantly affected the Company's Dividend Payout Ratio. Both are partial only variable Current Ratio (CR), which significantly influence the Dividend Payout Ratio.